Jumlah Eritrosit Tikus Putih (Rattus norvegicus) Strain Wistar Bunting yang Mengonsumsi MSG Organik dan Sintetis - Febriyanti, Amalia; Setyaningsih, Endang; Fauziah, Daniar Eka Nur; Aryanti, Firma; Sagita, Ninit Putry; Febrianti, Ulya Ananda Putri; Tias, Eriza Putri Ayu Ning; Wicaksono, M. Galih (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the number of erythrocytes in pregnant Wistar strain white rats (Rattus norvegicus) consuming organic and synthetic MSG. This study used a Completely Randomized Design (CRD) with 21 samples, 7 treatments, and 3 replications; control treatment (normal feed), P1 (60 mg/kgBW organic MSG), P2 (120 mg/kgBW organic MSG), P3 (240 mg/kgBW organic MSG), P4 (60 mg/kgBW synthetic MSG), P5 (120 mg/kgBW synthetic MSG), and P6 (240 mg/kgBW synthetic MSG). The analysis includes the number of erythrocytes in white rats (Rattus norvegicus), One Way ANOVA test using SPSS version 29, followed by Duncan’s Multiple Range Test (DMRT) to determine the mean differences between treatments. The research results show that the number of erythrocytes in the control group (normal) was 6.97 x 106 / ÂµL, P1 (5.17 x 106 / ÂµL), P2 (5.37 x 106 / ÂµL), P3 (5.89 x 106 / ÂµL), P4 (7.61 x 106 / ÂµL), P5 (7.90 x 106 / ÂµL), and P6 (8.29 x 106 / ÂµL). Thus, the administration of organic and synthetic MSG affects the number of erythrocytes in pregnant white rats (Rattus norvegicus) of the Wistar strain, marked by an increase in the number of erythrocytes. The lowest number of erythrocytes was in P1 (60 mg/kgBB), and the highest number of erythrocytes was in P6 (240 mg/kgBB).